Life´s style and its impact in general and oral health´s status of elderly in elderly´s house of Chorrillos - Ysla Cheé, Rosa (2020)
Objective: To determine the impact of the Older Adult's lifestyle on their general and oral health. Material and Method: descriptive, cross-sectional study in a sample of 44 older adults, of both sexes, who attended the Casa del Adult Mayor de Chorrillos, in Lima, Peru, November 2014. Socio-demographic data, a medical history were recorded dentistry and a questionnaire on diet, general health, physical and intellectual activity and oral hygiene habits was applied. The scores were very healthy, healthy and unhealthy lifestyle. In the oral examination, the CPOD, CPITN, Löe and Silness Gingival Index and IHOS indices were applied. The participants signed an informed consent. Results: 84.1% of older adults showed an “Unhealthy” lifestyle. The most prevalent systemic diseases were high blood pressure, eye problems, osteoarticular problems and diabetes. A high DMFT was observed, 19.98 ± 6.45 and at least 75% of older adults required periodontal treatment. Only 11.6% of the participants registered good oral hygiene. No statistical association was found between Lifestyle and DMFT, Löe Silness gingival index, CPITN, and IHOS, Chi square (p> 0.05). Conclusions: The percentage of "unhealthy" lifestyle is very high in this population, as well as the presence of cavities and periodontal disease. No association was found between the lifestyle of the elderly and their oral and general health.